Microbubble workover fluid and preparation process thereof

CN122587676BActive Publication Date: 2026-10-27SHAANXI HYDROGEN CHEN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611081182.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-27
Estimated Expiration
2046-07-21

AI Technical Summary

Technical Problem

[0005]该技术方案中,稳泡剂中的羧甲基淀粉、羧乙基淀粉主要通过增粘作用延缓泡沫排液,所形成的液膜强度较低,缺乏刚性界面结构支撑,抗排液与抗聚并能力较弱;此外,该方案将溶剂、发泡剂、稳泡剂和增黏剂一步混合,发泡与稳泡过程容易相互干扰,微泡粒径不均、界面膜结构不致密,泡沫均匀性与稳定性不足

Benefits of technology

本申请A剂中异构脂肪醇聚氧乙烯醚磷酸酯与支链烷基糖苷复配,在高矿化度盐水中形成致密混合吸附膜,提供发泡能力;B剂中经疏水型与亲水型硅烷偶联剂复合改性的植物纤维和纳米SiO2吸附于气液界面,微米纤维与纳米颗粒协同构成多尺度颗粒层,阻止气泡聚并;羟基聚合物与聚阴离子纤维素形成连续相网络,增粘提切、强化液膜并形成致密滤饼,实现低滤失。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122587676B_ABST
    Figure CN122587676B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of oil and gas field development aids, and particularly discloses a micro-bubble workover fluid and a preparation process thereof. The micro-bubble workover fluid is prepared from the following raw materials in parts by mass: 2-3 parts of A agent, 0.8-2.1 parts of B agent, and the rest water, with the total amount being 100 parts; the A agent comprises isomeric fatty alcohol polyoxyethylene ether phosphate and branched alkyl glucoside; and the B agent comprises poly-anion cellulose, amphiphilic modified plant fiber, hydroxyl polymer and amphiphilic modified nano SiO2. The micro-bubble workover fluid prepared by the application is stable in foam, has good plugging effect and excellent lubricating performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of oil and gas field development additives, and more specifically, to a microbubble well workover fluid and its preparation process. Background Technology

[0002] During oil and gas field development and production, as extraction time continues, formation pressure gradually decreases, and the number of low-pressure, easily leaking oil and gas wells increases year by year. In well workover operations, workover fluid, as a circulating working medium, plays a crucial role in carrying solid particles, balancing formation pressure, cooling, and lubricating tools. However, when the formation pressure coefficient is low, conventional workover fluids, due to their high density, have a fluid column pressure far exceeding the formation pore pressure, making them highly susceptible to differential pressure leakage. When a large amount of workover fluid leaks into the reservoir, the solid particles, inorganic salts, and chemical additives within it clog pore throats, causing an irreversible decrease in reservoir permeability. Simultaneously, filtrate intrusion can trigger various reservoir damages, such as the expansion and migration of water-sensitive minerals, water-locking effects, and crude oil emulsification. In severe cases, this can lead to a decline in oil and gas well production, or even complete loss of production capacity.

[0003] To address the aforementioned issues, microbubble workover fluids introduce a large number of uniformly dispersed micron-sized bubbles into the liquid phase. Combined with their low-density characteristics, this significantly reduces fluid column pressure and effectively controls leakage. Compared to conventional foam fluids, microbubbles have a thicker liquid film and stronger structural stability, maintaining their shape during wellbore circulation. They combine the low-density characteristics of foam with the sand-carrying capacity of conventional fluids.

[0004] Patent application CN117987102A discloses a foamed well workover fluid comprising the following components: solvent, foaming agent, foam stabilizer, and viscosity modifier; wherein the foaming agent comprises sodium dodecylbenzenesulfonate and isopropanolamine dodecyl; and / or the foam stabilizer comprises carboxymethyl starch, carboxyethyl starch, and polyanionic cellulose; and / or the viscosity modifier comprises xanthan gum, sodium carboxymethyl cellulose, and potassium chloride; wherein the preparation method of the foamed well workover fluid comprises: mixing the solvent, foaming agent, foam stabilizer, and viscosity modifier uniformly.

[0005] In this technical solution, the carboxymethyl starch and carboxyethyl starch in the foam stabilizer mainly delay the drainage of foam through thickening. The resulting liquid film has low strength and lacks rigid interfacial structure support, resulting in weak resistance to drainage and aggregation. In addition, this solution mixes the solvent, foaming agent, foam stabilizer and thickener in one step, which makes the foaming and foam stabilization processes prone to mutual interference. The microbubble particle size is uneven, the interfacial film structure is not dense, and the foam uniformity and stability are insufficient. Summary of the Invention

[0006] In order to overcome the shortcomings of existing foam workover fluids in terms of foam stabilization and foaming, this application provides a microbubble workover fluid and its preparation process.

[0007] This application provides a microbubble well workover fluid, which is prepared from the following raw materials in parts by weight: Agent A consists of 2-3 parts, Agent B consists of 0.8-2.1 parts, and the remainder is water, for a total of 100 parts; Agent A comprises isomeric fatty alcohol polyoxyethylene ether phosphate and branched alkyl glycosides; Agent B comprises polyanionic cellulose, amphiphilic modified plant fiber, hydroxyl polymer, and amphiphilic modified nano-SiO2; The hydroxy polymer is copolymerized from acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, hydroxyethyl acrylate, acryloylmorpholine and phosphorus / metal polymerizable monomers; The amphiphilic modified plant fiber is obtained by alkalizing plant fiber and then modifying it with a silane coupling agent containing hydrophobic groups and a silane coupling agent containing hydrophilic groups. The amphiphilic modified nano-SiO2 is prepared by modifying nano-SiO2 with a silane coupling agent containing hydrophobic groups and a silane coupling agent containing hydrophilic groups.

[0008] In this scheme, Agent A adopts a compound system of isomeric fatty alcohol polyoxyethylene ether phosphate and branched alkyl glycosides, providing excellent initial foaming ability; the rheology of the system is regulated by polyanionic cellulose to provide basic foam stabilization, and combined with the three-dimensional composite particle film formed by amphiphilic modified plant fiber and amphiphilic modified nano-SiO2 at the gas-liquid interface, it synergistically inhibits gravity drainage and bubble aggregation of foam; the hydroxy polymer, by introducing phosphorus / metal polymerizable monomers, achieves efficient filtration loss reduction and adsorption friction reduction; the amphiphilic modified plant fiber also has the function of microcrack sealing. The overall system realizes multi-functional integration of foaming, foam stabilization, filtration loss reduction, friction reduction and sealing, significantly reducing the damage to the reservoir caused by well workover operations.

[0009] More preferably, in agent A, the mass ratio of isomeric fatty alcohol polyoxyethylene ether phosphate to branched alkyl glycoside is (2~4):1.

[0010] More preferably, in agent B, the mass ratio of polyanionic cellulose, amphiphilic modified plant fiber, hydroxyl polymer and amphiphilic modified nano-SiO2 is (0.1~0.5):(0.1~0.3):(0.5~1.0):(0.1~0.5).

[0011] Preferably, the method for preparing the hydroxyl polymer includes the following steps: Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, hydroxyethyl acrylate, acrylmorpholine, and phosphorus / metal polymerizable monomers were added to an aqueous ethanol solution and neutralized. Under an inert atmosphere, an initiator was added, the temperature was raised to 50-60°C, and the reaction was carried out for 3.5-4.5 hours. After cooling, precipitation, washing, and drying, the hydroxyl polymer was obtained.

[0012] Preferably, the mass ratio of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, hydroxyethyl acrylate, acrylmorpholine and phosphorus / metal polymerizable monomer is (40~50):(20~30):(5~10):(10~15):(5~10).

[0013] In this scheme, the hydroxyl polymer uses acrylamide as the main chain backbone. The introduction of 2-acrylamido-2-methylpropanesulfonic acid endows the polymer with excellent temperature and salt resistance. Its sulfonic acid groups can enhance the hydration ability of the molecular chain, improve the temperature and salt resistance of the polymer, and slow down the performance decay of the molecular chain and amide groups under high temperature conditions. Hydroxyethyl acrylate provides hydroxyl crosslinking sites to enhance the hydrogen bonding with amphiphilic particles; acrylmorpholine enhances the thermal stability and shear resistance of the molecular chain through its cyclic rigid structure; phosphorus-containing / metal polymerizable monomers covalently anchor phosphate esters or metal ions to the molecular chain, endowing the polymer with strong adsorption and film-forming ability on metal surfaces, forming a dense lubricating protective film on the friction pair surface, and synergistically achieving the integrated function of reducing filtration loss and reducing friction and wear.

[0014] Preferably, the phosphorus-containing / metal polymerizable monomer is 2-hydroxyethyl methacrylate phosphate or zinc methacrylate.

[0015] In this solution, 2-hydroxyethyl methacrylate phosphate has phosphate ester active groups, which can be adsorbed onto the metal surface to enhance lubrication and film-forming ability; zinc methacrylate can form ionic crosslinks between molecular chains, improving the overall strength and density of the polymer film. Both can be grafted onto the polymer backbone to achieve reduced filtration loss and friction reduction / wear resistance.

[0016] Preferably, the isomeric fatty alcohol polyoxyethylene ether phosphate is at least one of isomeric tridecyl alcohol polyoxyethylene ether phosphate and isomeric decayl alcohol polyoxyethylene ether phosphate.

[0017] In this solution, the branched alkyl chain structure gives it superior temperature and salt resistance and interfacial activity compared to straight-chain phosphate esters. When combined with branched alkyl glycosides, it can produce a significant synergistic foaming effect, which can increase the initial foaming volume of the system and improve the fineness of the foam. At the same time, it has good compatibility with anionic and nonionic components such as polyanionic cellulose and hydroxy polymers in the system, and also has certain wetting and emulsifying properties, which helps to improve the overall operational performance of the microbubble well workover fluid.

[0018] Preferably, the branched alkyl glycoside is a C8-11 branched alkyl glucoside.

[0019] In this formulation, the branched alkyl chain structure endows it with superior temperature and salt resistance and interfacial activity compared to straight-chain alkyl glucosides. When combined with isomeric fatty alcohol polyoxyethylene ether phosphate, it produces a significant synergistic foaming and stabilizing effect, further improving foam stability and refining microbubble particle size. The multiple hydroxyl groups on its glycosidic ring structure can form strong hydrogen bonds with water molecules, binding free water in the foam liquid film, slowing down the drainage rate, and assisting in foam stabilization at the molecular level.

[0020] Furthermore, the method for preparing the amphiphilic modified plant fiber includes the following steps: (1) After alkalizing the plant fibers, washing and drying them, pretreated plant fibers are obtained; (2) Disperse the pretreated plant fiber in an ethanol aqueous solution, add a silane coupling agent containing a hydrophobic group and a silane coupling agent containing a hydrophilic group, adjust the pH to 4.0~4.5, raise the temperature to 65~75℃, react for 3~5h, separate the solid and liquid, wash, dry, and obtain amphiphilic modified plant fiber.

[0021] Furthermore, the mass ratio of the pretreated plant fiber, the silane coupling agent containing hydrophobic groups, and the silane coupling agent containing hydrophilic groups is 100:(3~5):(2~4).

[0022] Furthermore, the silane coupling agent containing hydrophobic groups is hexadecyltrimethoxysilane.

[0023] Furthermore, the silane coupling agent containing the hydrophilic group is any one of γ-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0024] In this scheme, a one-step amphiphilic modification of plant fibers after alkalization pretreatment is carried out by combining hydrophobic and hydrophilic silane coupling agents. By simultaneously grafting hydrophobic alkyl chains and hydrophilic amino groups onto the fiber surface, the hydrophobic-hydrophilic balance on the fiber surface is precisely controlled. The modified plant fibers exhibit excellent dispersibility in water-based systems, with no risk of agglomeration and sedimentation. They adsorb at the gas-liquid interface to help enhance the mechanical strength of the liquid film. At the same time, the modified fibers still have a certain skeletal support function, which can form an auxiliary bridge between the filter cake and the near-wellbore formation, and work together with nanoparticles to seal formation microfractures.

[0025] More preferably, the alkalization of plant fibers specifically involves: immersing plant fibers in a sodium hydroxide solution with a mass concentration of 5% to 10%, mixing for 40 to 60 minutes, and then separating the solid and liquid components.

[0026] Furthermore, the preparation method of the amphiphilic modified nano-SiO2 includes the following steps: Nano-SiO2 was dispersed in an aqueous ethanol solution, and silane coupling agents containing hydrophobic and hydrophilic groups were added. The pH was adjusted to 4.0-4.5, the temperature was raised to 65-75℃, and the reaction was carried out for 3-5 hours. After solid-liquid separation, washing and drying, amphiphilic modified nano-SiO2 was obtained.

[0027] In this scheme, by simultaneously grafting hydrophobic alkyl chains and hydrophilic amino groups onto the surface of nanoparticles, the modified nano-SiO2 exhibits excellent dispersibility in aqueous systems and adsorbs onto the gas-liquid interface to form a dense nanoparticle film, significantly enhancing the mechanical strength and rupture resistance of the liquid film. It also exhibits a good synergistic effect with amphiphilic modified plant fibers, and the two together construct a composite interface framework, further improving the temperature and salt resistance stability of microbubbles. It can fill the tiny pores inside the filter cake and work synergistically with the microbubble system to enhance the sealing effect, thereby reducing filtration loss.

[0028] Furthermore, the mass ratio of the nano-SiO2, the silane coupling agent containing hydrophobic groups, and the silane coupling agent containing hydrophilic groups is 100:(3~5):(2~4).

[0029] More preferably, agent B further includes 0.1 to 0.2 parts by weight of polyethylene glycol dioleate.

[0030] In this scheme, the long dioleic acid chain of polyethylene glycol dioleate can penetrate deep into the bubble interface to form a denser mixed adsorption layer with agent A, while the polyethylene glycol segments extend into the aqueous phase to provide steric hindrance, thereby optimizing the fineness and stability of the foam and helping to reduce the foam decay rate under high shear conditions.

[0031] Preferably, agent A further comprises 0.15 to 0.25 parts by weight of polyether F68.

[0032] In this design, polyether F68 is a PEO-PPO-PEO triblock copolymer, with PPO blocks forming the hydrophobic portion and PEO blocks on both sides forming the hydrophilic portion. As the temperature increases, the hydrophobicity of the PPO blocks increases, driving the formation of micelles. The long PEO chains extend into the aqueous phase to form a steric hydration layer, preventing microbubble aggregation and improving stability.

[0033] This application also provides a process for preparing microbubble well workover fluid, comprising the following steps: S1: Mix some water and agent A evenly to obtain a premixed solution; S2: Mix the remaining water and agent B evenly, add the premixed liquid, mix evenly, and introduce a mixture of compressed air and nitrogen with a gas-liquid ratio of (8~10):1 to obtain microbubble well repair fluid.

[0034] In this scheme, agent A is preferentially dispersed in a portion of the water, allowing surfactant molecules to pre-hydrate and form an initial gas-liquid interface under preliminary stirring and shearing. Agent B components are fully dispersed and swollen in the remaining water before being combined with the premixed solution. This ensures that the amphiphilic modified plant fibers, amphiphilic modified nano-SiO2, and hydroxyl polymers are adsorbed and cross-linked on the pre-constructed microbubble interface. After merging, a mixture of compressed air and nitrogen is introduced. The shearing effect generated by the gas injection further refines the microbubbles, while the introduction of nitrogen reduces the dissolved oxygen content in the system, slowing down the oxidative degradation of organic components under high-temperature downhole conditions. The gas-liquid ratio is controlled at (8~10):1 to achieve a suitable density and bubble diameter distribution in the final microbubble system, balancing the need for low-density sand carrying capacity with foam stability. The overall process strictly follows the feeding sequence of first initiating foaming and then stabilizing it. The steps are simple, require no special equipment, and facilitate continuous on-site mixing operations.

[0035] More preferably, the pressure of the compressed air is 0.7~0.8 MPa.

[0036] In summary, this application has the following beneficial effects: In Agent A of this application, isomeric fatty alcohol polyoxyethylene ether phosphate is compounded with branched alkyl glycosides to form a dense mixed adsorption film in highly mineralized brine, providing foaming capacity. In Agent B, plant fibers modified with hydrophobic and hydrophilic silane coupling agents and nano-SiO2 are adsorbed at the gas-liquid interface. Micron fibers and nanoparticles synergistically form a multi-scale particle layer, preventing bubble aggregation. Hydroxy polymers and polyanionic cellulose form a continuous phase network, which thickens and shears, strengthens the liquid film, and forms a dense filter cake, achieving low filtration loss. Attached Figure Description

[0037] Figure 1 The image shows the microscopic morphology of the microbubble well-drainage fluid prepared in Example 1 of this application under an optical microscope. Detailed Implementation

[0038] The present application will be further described in detail below with reference to the embodiments.

[0039] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.

[0040] The branched alkyl glycosides are C8~11 branched alkyl glucosides, JFC-2G, purchased from Hubei Kewode Chemical Co., Ltd.

[0041] Preparation Examples 1-3: Hydroxy Polymers Preparation Example 1 The preparation method of the hydroxyl polymer in this example includes the following steps: 120g of acrylamide, 90g of 2-acrylamido-2-methylpropanesulfonic acid, 30g of hydroxyethyl acrylate, 30g of acrylmorpholine, and 30g of 2-hydroxyethyl methacrylate phosphate were added to 1000mL of an ethanol-water solution (anhydrous ethanol to water volume ratio of 1:9). The mixture was stirred at 200rpm until homogeneous. The pH was adjusted to 6.5 using a 5% sodium hydroxide solution. Nitrogen gas was bubbled through the mixture for 20min to remove oxygen, maintaining a slight positive pressure (0.02~0.03MPa). 0.3g of ammonium persulfate and 0.3g of sodium bisulfite were added and stirred until homogeneous. The mixture was heated to 50℃ and reacted for 4.5h. After the reaction was completed, the mixture was cooled to room temperature. The reaction solution was poured into twice the volume of cold acetone to precipitate the precipitate. The precipitate was filtered, washed twice with cold acetone, and dried under vacuum at 60℃ to constant weight. The precipitate was then pulverized to obtain the hydroxy polymer.

[0042] Preparation Example 2 The preparation method of the hydroxyl polymer in this example includes the following steps: 150g of acrylamide, 60g of 2-acrylamido-2-methylpropanesulfonic acid, 15g of hydroxyethyl acrylate, 45g of acrylmorpholine, and 30g of zinc methacrylate were added to 1000mL of an ethanol-water solution (anhydrous ethanol to water volume ratio of 1:9). The mixture was stirred at 200rpm until homogeneous. The pH was adjusted to 7.0 using a 5% sodium hydroxide solution. Nitrogen gas was bubbled through the mixture for 20min to remove oxygen, maintaining a slight positive pressure (0.02~0.03MPa). 0.5g of ammonium persulfate and 0.5g of sodium bisulfite were added and stirred until homogeneous. The mixture was heated to 55℃ and reacted for 4h. After the reaction was completed, the mixture was cooled to room temperature. The reaction solution was poured into twice the volume of cold acetone to precipitate the precipitate. The precipitate was filtered, washed twice with cold acetone, and dried under vacuum at 60℃ to constant weight. The precipitate was then pulverized to obtain the hydroxyl polymer.

[0043] Preparation Example 3 The preparation method of the hydroxyl polymer in this example includes the following steps: 135g of acrylamide, 75g of 2-acrylamido-2-methylpropanesulfonic acid, 30g of hydroxyethyl acrylate, 45g of acrylmorpholine, and 15g of zinc methacrylate were added to 1000mL of an ethanol-water solution (anhydrous ethanol to water volume ratio of 1:9). The mixture was stirred at 200rpm until homogeneous. The pH was adjusted to 6.5 using a 5% sodium hydroxide solution. Nitrogen gas was bubbled through the mixture for 20min to remove oxygen, maintaining a slight positive pressure (0.02~0.03MPa). 0.6g of ammonium persulfate and 0.6g of sodium bisulfite were added and stirred until homogeneous. The mixture was heated to 60℃ and reacted for 3.5h. After the reaction was completed, the mixture was cooled to room temperature. The reaction solution was poured into twice the volume of cold acetone to precipitate the precipitate. The precipitate was filtered, washed twice with cold acetone, and dried under vacuum at 60℃ to constant weight. The precipitate was then pulverized to obtain the hydroxyl polymer.

[0044] Preparation Examples 4-6: Amphiphilic Modified Plant Fibers Preparation Example 4 The preparation method of the amphiphilic modified plant fiber in this example includes the following steps: (1) Bamboo fiber was immersed in a 5% sodium hydroxide solution with a solid-liquid ratio of 1g:8mL. The mixture was stirred at 200rpm for 60min, filtered, washed with deionized water until neutral, and vacuum dried at 60℃ to constant weight to obtain pretreated plant fiber. (2) 100g of pretreated plant fiber was dispersed in 1000mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water was 9:1), 3g of hexadecyltrimethoxysilane and 2g of γ-aminopropyltriethoxysilane were added, the pH was adjusted to 4.5 with 10% glacial acetic acid, the temperature was raised to 65℃, and the reaction was carried out for 5h. After the reaction was completed, the mixture was filtered, the filter cake was washed twice with anhydrous ethanol, and the mixture was vacuum dried at 60℃ to constant weight. The mixture was then ground and dispersed to obtain amphiphilic modified plant fiber with a length distribution of about 50~100μm.

[0045] Preparation Example 5 The preparation method of the amphiphilic modified plant fiber in this example includes the following steps: (1) Bamboo fiber was immersed in a 10% sodium hydroxide solution with a solid-liquid ratio of 1g:8mL. The mixture was stirred at 200rpm for 60min, filtered, washed with deionized water until neutral, and vacuum dried at 60℃ to constant weight to obtain pretreated plant fiber. (2) 100g of pretreated plant fiber was dispersed in 1000mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water was 9:1), 4g of hexadecyltrimethoxysilane and 3g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane were added, the pH was adjusted to 4.0 with 10% glacial acetic acid, the temperature was raised to 70℃, and the reaction was carried out for 4h. After the reaction was completed, the mixture was filtered, the filter cake was washed twice with anhydrous ethanol, and the mixture was vacuum dried at 60℃ to constant weight. The mixture was then ground and dispersed to obtain amphiphilic modified plant fiber with a length distribution of about 50~100μm.

[0046] Preparation Example 6 The preparation method of the amphiphilic modified plant fiber in this example includes the following steps: (1) Bamboo fiber was immersed in a 10% sodium hydroxide solution with a solid-liquid ratio of 1g:8mL. The mixture was stirred at 200rpm for 60min, filtered, washed with deionized water until neutral, and vacuum dried at 60℃ to constant weight to obtain pretreated plant fiber. (2) 100g of pretreated plant fiber was dispersed in 1000mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water was 9:1), 5g of hexadecyltrimethoxysilane and 4g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane were added, the pH was adjusted to 4.0 with 10% glacial acetic acid, the temperature was raised to 75℃, and the reaction was carried out for 3h. After the reaction was completed, the mixture was filtered, the filter cake was washed twice with anhydrous ethanol, and the mixture was vacuum dried at 60℃ to constant weight. The mixture was then ground and dispersed to obtain amphiphilic modified plant fiber with a length distribution of about 50~100μm.

[0047] Preparation Examples 7-9: Amphiphilic Modified Nano-SiO2 Preparation Example 7 The preparation method of amphiphilic modified nano-SiO2 in this example includes the following steps: 100g of nano-SiO2 was dispersed in 1000mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water was 9:1). 3g of hexadecyltrimethoxysilane and 2g of γ-aminopropyltriethoxysilane were added. The pH was adjusted to 4.5 with 10% glacial acetic acid. The temperature was raised to 65℃ and the reaction was carried out for 5h. After the reaction was completed, the mixture was filtered, and the filter cake was washed twice with anhydrous ethanol. The mixture was then vacuum dried at 60℃ to constant weight, ground and dispersed to obtain amphiphilic modified nano-SiO2.

[0048] The particle size distribution of nano-SiO2 is 20~50nm.

[0049] Preparation Example 8 The preparation method of amphiphilic modified nano-SiO2 in this example includes the following steps: 100g of nano-SiO2 was dispersed in 1000mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water was 9:1). 4g of hexadecyltrimethoxysilane and 3g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane were added. The pH was adjusted to 4.0 with 10% glacial acetic acid. The temperature was raised to 70℃ and the reaction was carried out for 4h. After the reaction was completed, the mixture was filtered, the filter cake was washed twice with anhydrous ethanol, and then dried under vacuum at 60℃ to constant weight. The mixture was then ground and dispersed to obtain amphiphilic modified nano-SiO2.

[0050] The particle size distribution of nano-SiO2 is 20~50nm.

[0051] Preparation Example 9 The preparation method of amphiphilic modified nano-SiO2 in this example includes the following steps: 100g of nano-SiO2 was dispersed in 1000mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water was 9:1). 5g of hexadecyltrimethoxysilane and 4g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane were added. The pH was adjusted to 4.0 with 10% glacial acetic acid. The temperature was raised to 75℃ and the reaction was carried out for 3h. After the reaction was completed, the mixture was filtered, the filter cake was washed twice with anhydrous ethanol, dried under vacuum at 60℃ to constant weight, and then ground and dispersed to obtain amphiphilic modified nano-SiO2.

[0052] The particle size distribution of nano-SiO2 is 20~50nm.

[0053] Example 1 The preparation process of the microbubble well workover fluid in this embodiment includes the following steps: S1: Add 50% water and agent A to a container and stir at 150 rpm for 6 minutes to obtain mixture A; S2: Add 50% water and agent B to a container and stir at 80 rpm for 15 minutes. Slowly add mixture A and stir at 200 rpm for 5 minutes. Transfer to a mixing device, set the power to 3 kW, maintain the shear speed at 2000 rpm, and run continuously for 20 minutes to obtain a mixed solution. Transfer the mixed solution to a microbubble generator and introduce a mixture of compressed air (pressure 0.7 MPa) and nitrogen with a volume ratio of 50:50 and a gas-liquid ratio of 8:1 until stable microbubbles with a bubble diameter of 50~300 μm are formed to obtain microbubble well workover fluid.

[0054] Among them, Agent A consists of 3g of isotridecyl polyoxyethylene ether phosphate and 1g of branched alkyl glycoside; Agent B consists of 0.2 g of polyanionic cellulose, 0.2 g of amphiphilic modified plant fiber from Preparation Example 4, 1 g of hydroxyl polymer from Preparation Example 1, and 0.2 g of amphiphilic modified nano-SiO2 from Preparation Example 7; the total amount of water is 193.4 g.

[0055] Example 2 The preparation process of the microbubble well workover fluid in this embodiment includes the following steps: S1: Add 50% water and agent A to a container and stir at 150 rpm for 6 minutes to obtain mixture A; S2: Add 50% water and agent B to a container and stir at 80 rpm for 15 minutes. Slowly add mixture A and stir at 200 rpm for 5 minutes. Transfer to a mixing device, set the power to 3 kW, maintain the shear speed at 2000 rpm, and run continuously for 20 minutes to obtain a mixed solution. Transfer the mixed solution to a microbubble generator and introduce a mixture of compressed air (pressure 0.8 MPa) and nitrogen with a volume ratio of 50:50 and a gas-liquid ratio of 10:1 until stable microbubbles with a bubble diameter of 50~300 μm are formed to obtain microbubble well workover fluid.

[0056] Among them, Agent A consists of 4g of isotridecyl polyoxyethylene ether phosphate and 1g of branched alkyl glycoside; Agent B consists of 0.6 g of polyanionic cellulose, 0.4 g of amphiphilic modified plant fiber from Preparation Example 5, 1.5 g of hydroxyl polymer from Preparation Example 2, and 0.5 g of amphiphilic modified nano-SiO2 from Preparation Example 8; the total amount of water is 192 g.

[0057] Example 3 The preparation process of the microbubble well workover fluid in this embodiment includes the following steps: S1: Add 50% water and agent A to a container and stir at 150 rpm for 6 minutes to obtain mixture A; S2: Add 50% water and agent B to a container and stir at 80 rpm for 15 minutes. Slowly add mixture A and stir at 200 rpm for 5 minutes. Transfer to a mixing device, set the power to 3 kW, maintain the shear speed at 2000 rpm, and run continuously for 20 minutes to obtain a mixed solution. Transfer the mixed solution to a microbubble generator and introduce a mixture of compressed air (pressure 0.8 MPa) and nitrogen with a volume ratio of 50:50 and a gas-liquid ratio of 10:1 until stable microbubbles with a bubble diameter of 50~300 μm are formed to obtain microbubble well workover fluid.

[0058] Among them, Agent A consists of 3g of isotridecyl alcohol polyoxyethylene ether phosphate, 1g of isodecyl alcohol polyoxyethylene ether phosphate, and 2g of branched alkyl glycoside. Agent B consists of 1g of polyanionic cellulose, 0.6g of amphiphilic modified plant fiber from Preparation Example 6, 2g of hydroxyl polymer from Preparation Example 3, and 0.6g of amphiphilic modified nano-SiO2 from Preparation Example 9; the total amount of water is 189.8g.

[0059] Example 4 The preparation process of the microbubble well workover fluid in this embodiment includes the following steps: S1: Add 50% water and agent A to a container and stir at 150 rpm for 6 minutes to obtain mixture A; S2: Add 50% water and agent B to a container and stir at 80 rpm for 15 minutes. Slowly add mixture A and stir at 200 rpm for 5 minutes. Transfer to a mixing device, set the power to 3 kW, maintain the shear speed at 2000 rpm, and run continuously for 20 minutes to obtain a mixed solution. Transfer the mixed solution to a microbubble generator and introduce a mixture of compressed air (pressure 0.8 MPa) and nitrogen with a volume ratio of 50:50 and a gas-liquid ratio of 10:1 until stable microbubbles with a bubble diameter of 50~300 μm are formed to obtain microbubble well workover fluid.

[0060] Among them, Agent A consists of 4g of isotridecyl polyoxyethylene ether phosphate and 1g of branched alkyl glycoside; Agent B consists of 0.6 g of polyanionic cellulose, 0.4 g of amphiphilic modified plant fiber from Preparation Example 6, 1.5 g of hydroxyl polymer from Preparation Example 3, 0.5 g of amphiphilic modified nano-SiO2 from Preparation Example 9, and 0.2 g of polyethylene glycol dioleate; the total amount of water is 191.8 g.

[0061] Example 5 The preparation process of the microbubble well workover fluid in this embodiment includes the following steps: S1: Add 50% water and agent A to a container and stir at 150 rpm for 6 minutes to obtain mixture A; S2: Add 50% water and agent B to a container and stir at 80 rpm for 15 minutes. Slowly add mixture A and stir at 200 rpm for 5 minutes. Transfer to a mixing device, set the power to 3 kW, maintain the shear speed at 2000 rpm, and run continuously for 20 minutes to obtain a mixed solution. Transfer the mixed solution to a microbubble generator and introduce a mixture of compressed air (pressure 0.8 MPa) and nitrogen with a volume ratio of 50:50 and a gas-liquid ratio of 10:1 until stable microbubbles with a bubble diameter of 50~300 μm are formed to obtain microbubble well workover fluid.

[0062] Among them, Agent A consists of 4g of isotridecyl polyoxyethylene ether phosphate and 1g of branched alkyl glycoside; Agent B consists of 0.6 g of polyanionic cellulose, 0.4 g of amphiphilic modified plant fiber from Preparation Example 6, 1.5 g of hydroxyl polymer from Preparation Example 3, 0.5 g of amphiphilic modified nano-SiO2 from Preparation Example 9, and 0.4 g of polyethylene glycol dioleate; the total amount of water is 191.6 g.

[0063] Example 6 The preparation process of the microbubble well workover fluid in this embodiment includes the following steps: S1: Add 50% water and agent A to a container and stir at 150 rpm for 6 minutes to obtain mixture A; S2: Add 50% water and agent B to a container and stir at 80 rpm for 15 minutes. Slowly add mixture A and stir at 200 rpm for 5 minutes. Transfer to a mixing device, set the power to 3 kW, maintain the shear speed at 2000 rpm, and run continuously for 20 minutes to obtain a mixed solution. Transfer the mixed solution to a microbubble generator and introduce a mixture of compressed air (pressure 0.8 MPa) and nitrogen with a volume ratio of 50:50 and a gas-liquid ratio of 10:1 until stable microbubbles with a bubble diameter of 50~300 μm are formed to obtain microbubble well workover fluid.

[0064] Among them, Agent A consists of 4g of isotridecyl polyoxyethylene ether phosphate, 1g of branched alkyl glycoside, and 0.3g of polyether F68; Agent B consists of 0.6 g of polyanionic cellulose, 0.4 g of amphiphilic modified plant fiber from Preparation Example 6, 1.5 g of hydroxyl polymer from Preparation Example 3, 0.5 g of amphiphilic modified nano-SiO2 from Preparation Example 9, and 0.4 g of polyethylene glycol dioleate; the total amount of water is 191.3 g.

[0065] Example 7 The preparation process of the microbubble well workover fluid in this embodiment includes the following steps: S1: Add 50% water and agent A to a container and stir at 150 rpm for 6 minutes to obtain mixture A; S2: Add 50% water and agent B to a container and stir at 80 rpm for 15 minutes. Slowly add mixture A and stir at 200 rpm for 5 minutes. Transfer to a mixing device, set the power to 3 kW, maintain the shear speed at 2000 rpm, and run continuously for 20 minutes to obtain a mixed solution. Transfer the mixed solution to a microbubble generator and introduce a mixture of compressed air (pressure 0.8 MPa) and nitrogen with a volume ratio of 50:50 and a gas-liquid ratio of 10:1 until stable microbubbles with a bubble diameter of 50~300 μm are formed to obtain microbubble well workover fluid.

[0066] Among them, Agent A consists of 4g of isomeric tridecyl alcohol polyoxyethylene ether phosphate, 1g of branched alkyl glycoside, and 0.5g of polyether F68; Agent B consists of 0.6 g of polyanionic cellulose, 0.4 g of amphiphilic modified plant fiber from Preparation Example 6, 1.5 g of hydroxyl polymer from Preparation Example 3, 0.5 g of amphiphilic modified nano-SiO2 from Preparation Example 9, and 0.4 g of polyethylene glycol dioleate; the total amount of water is 191.1 g.

[0067] Comparative Example 1 The difference between this comparative example and Example 1 is as follows: Agent A is 4g of isotridecyl polyoxyethylene ether phosphate; Everything else is the same as in Example 1.

[0068] Comparative Example 2 The difference between this comparative example and Example 1 is as follows: Agent B consists of 0.2g of polyanionic cellulose, 0.2g of modified plant fiber, 1g of the hydroxyl polymer in Preparation Example 1, and 0.2g of amphiphilic modified nano-SiO2 in Preparation Example 7; the total amount of water is 194.4g.

[0069] The preparation method of modified plant fiber includes the following steps: (1) The plant fiber was immersed in a 5% sodium hydroxide solution with a solid-liquid ratio of 1g:8mL. The mixture was stirred at 200rpm for 60min, filtered, washed with deionized water until neutral, and dried under vacuum at 60℃ to constant weight to obtain pretreated plant fiber. (2) 100g of pretreated plant fiber was dispersed in 1000mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water was 9:1), 5g of hexadecyltrimethoxysilane was added, the pH was adjusted to 4.5 with 10% glacial acetic acid, the temperature was raised to 65℃, and the reaction was carried out for 5h. After the reaction was completed, the filter cake was filtered, washed twice with anhydrous ethanol, dried under vacuum at 60℃ to constant weight, ground and dispersed to obtain modified plant fiber with a length distribution of about 50~100μm.

[0070] Everything else is the same as in Example 1.

[0071] Comparative Example 3 The difference between this comparative example and Example 1 is as follows: No amphiphilic modified nano-SiO2 was added to Agent B.

[0072] Everything else is the same as in Example 1.

[0073] Comparative Example 4 The difference between this comparative example and Example 1 is as follows: Agent B consists of 0.2 g of polyanionic cellulose, 0.2 g of amphiphilic modified plant fiber from Preparation Example 4, 1 g of hydroxyl polymer, and 0.2 g of amphiphilic modified nano-SiO2 from Preparation Example 7; The preparation method of the hydroxyl polymer includes the following steps: 150g of acrylamide, 90g of 2-acrylamido-2-methylpropanesulfonic acid, 30g of hydroxyethyl acrylate, and 30g of acrylmorpholine were added to 1000g of an ethanol aqueous solution (the volume ratio of anhydrous ethanol to water was 1:9). The mixture was stirred at 200rpm until homogeneous. The pH was adjusted to 6.5 using a 5% sodium hydroxide solution. Nitrogen gas was bubbled through the mixture for 20min to remove oxygen, maintaining a slight positive pressure (0.02~0.03MPa). 0.3g of ammonium persulfate and 0.3g of sodium bisulfite were added and stirred until homogeneous. The mixture was heated to 50℃ and reacted for 4.5h. After the reaction was completed, the mixture was cooled to room temperature. The reaction solution was poured into twice the volume of cold acetone to precipitate the precipitate. The precipitate was filtered, washed twice with cold acetone, and dried under vacuum at 60℃ to constant weight. The precipitate was then pulverized to obtain the hydroxyl polymer.

[0074] Everything else is the same as in Example 1.

[0075] Performance testing (1) Test according to the method specified in GBT16783.1-2014 "Field Testing of Drilling Fluids for Petroleum and Natural Gas Industry - Part 1: Water-based Drilling Fluids"; (2) Test according to the method specified in SY / T6094-2024 "Evaluation Procedure for Lubricants for Drilling Fluids", and use an extreme pressure lubrication tester to test the lubrication coefficient reduction rate; (3) Use the Waring Blender method to stir 100 mL of workover fluid at 11000 r / min for 1 min, record the initial foam volume, and record the foam half-life at 25℃.

[0076] Table 1. Performance test data of microbubble well workover fluids prepared in Examples 1-7 and Comparative Examples 1-4

[0077] As can be seen from Examples 1-3, with the increase of the dosage of Agent A and Agent B, the foaming and stabilizing ability, rheological sand-carrying performance, plugging and filtration loss reduction performance, and lubrication and anti-wear performance of the system are all optimized simultaneously, and the overall performance of the workover fluid is steadily improved.

[0078] from Figure 1 It can be seen that the microbubble well-keeping fluid prepared in Example 1 contains a large number of uniformly sized, dense micron-sized bubbles, and the bubbles do not show obvious aggregation or bursting phenomena.

[0079] As can be seen from Examples 3-5, the introduction of polyethylene glycol dioleate effectively optimizes the gas-liquid interface film structure, improves the lubrication performance of the system, and further enhances the foam stability and plugging and filtration reduction capabilities, thus significantly improving the interfacial stability and lubrication and friction reduction performance of the microbubble well workover fluid.

[0080] As can be seen from Examples 5-7, the introduction of polyether F68 effectively improves the uniformity and long-term stability of the microbubble system, continuously optimizes the filtration loss control performance of the workover fluid, and maintains the excellent lubrication performance of the system.

[0081] Comparing Example 1 and Comparative Example 1, it can be seen that without the addition of branched alkyl glycosides, the overall foaming and stabilizing performance, lubrication performance, and plugging performance of the well workover fluid all decreased significantly, proving that the combination of branched alkyl glycosides and isomeric fatty alcohol polyoxyethylene ether phosphate can effectively construct a stable and efficient foaming system.

[0082] Comparing Example 1 and Comparative Example 2, it can be seen that when plant fibers are modified with hexadecyltrimethoxysilane alone, the foam stability and filtration performance of the system deteriorate significantly.

[0083] Comparing Example 1 and Comparative Example 3, it can be seen that without the addition of amphiphilic nano-SiO2, the system's bubble stabilization ability and filtration blockage performance are significantly reduced.

[0084] Comparing Example 1 and Comparative Example 4, it can be seen that when the functional monomer 2-hydroxyethyl methacrylate phosphate was not added during the synthesis of the hydroxy polymer, the lubrication and friction reduction performance of the well workover fluid was significantly reduced, while the filtration loss control performance decreased slightly.

Claims

1. A microbubble well-workover fluid, characterized in that, The product is prepared from the following raw materials in parts by weight: 2-3 parts of Agent A, 0.8-2.1 parts of Agent B, and the remainder is water, for a total of 100 parts; Agent A includes isomeric fatty alcohol polyoxyethylene ether phosphate and branched alkyl glycosides; Agent B includes polyanionic cellulose, amphiphilic modified plant fiber, hydroxy polymer, and amphiphilic modified nano-SiO2; The hydroxy polymer is copolymerized from acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, hydroxyethyl acrylate, acryloylmorpholine, and phosphorus / metal polymerizable monomers, wherein the phosphorus / metal polymerizable monomers are 2-hydroxyethyl methacrylate phosphate or zinc methacrylate; The amphiphilic modified plant fiber is obtained by alkalizing plant fiber and then modifying it with a silane coupling agent containing hydrophobic groups and a silane coupling agent containing hydrophilic groups; The amphiphilic modified nano-SiO2 is obtained by modifying nano-SiO2 with a silane coupling agent containing hydrophobic groups and a silane coupling agent containing hydrophilic groups.

2. The microbubble well-workover fluid according to claim 1, characterized in that, In Agent A, the mass ratio of isomeric fatty alcohol polyoxyethylene ether phosphate to branched alkyl glycoside is (2~4):

1.

3. The microbubble well-workover fluid according to claim 1, characterized in that, In Agent B, the mass ratio of polyanionic cellulose, amphiphilic modified plant fiber, hydroxyl polymer and amphiphilic modified nano-SiO2 is (0.1~0.5):(0.1~0.3):(0.5~1.0):(0.1~0.5).

4. The microbubble well-workover fluid according to claim 1, characterized in that, The method for preparing the hydroxy polymer includes the following steps: adding acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, hydroxyethyl acrylate, acrylmorpholine and phosphorus / metal polymerizable monomers to an aqueous ethanol solution, neutralizing, adding an initiator under an inert atmosphere, heating to 50~60℃, reacting for 3.5~4.5h, cooling, precipitating, washing, and drying to obtain the hydroxy polymer.

5. The microbubble well-workover fluid according to claim 1, characterized in that, The preparation method of the amphiphilic modified plant fiber includes the following steps: (1) after alkalizing the plant fiber, washing and drying it, the pretreated plant fiber is obtained; (2) the pretreated plant fiber is dispersed in an ethanol aqueous solution, a silane coupling agent containing a hydrophobic group and a silane coupling agent containing a hydrophilic group are added, the pH is adjusted to 4.0~4.5, the temperature is raised to 65~75℃, the reaction is carried out for 3~5h, the solid and liquid are separated, washed and dried to obtain the amphiphilic modified plant fiber.

6. The microbubble well-workover fluid according to claim 1, characterized in that, The preparation method of the amphiphilic modified nano-SiO2 includes the following steps: dispersing nano-SiO2 in an ethanol aqueous solution, adding a silane coupling agent containing a hydrophobic group and a silane coupling agent containing a hydrophilic group, adjusting the pH to 4.0~4.5, heating to 65~75℃, reacting for 3~5h, separating the solid and liquid, washing, and drying to obtain amphiphilic modified nano-SiO2.

7. The microbubble well-workover fluid according to claim 5 or 6, characterized in that, The silane coupling agent containing hydrophobic groups is hexadecyltrimethoxysilane.

8. The microbubble well-workover fluid according to claim 5 or 6, characterized in that, The silane coupling agent containing a hydrophilic group is either γ-aminopropyltriethoxysilane or N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

9. A preparation process for the microbubble well workover fluid as described in claim 1, characterized in that, The process includes the following steps: S1: Mix a portion of water and agent A evenly to obtain a premixed solution; S2: Mix the remaining water and agent B evenly, add the premixed solution, mix evenly, and introduce a mixture of compressed air and nitrogen with a gas-liquid ratio of (8~10):1 to obtain a microbubble well-keeping fluid.

Citation Information

Patent Citations

  • Foam workover fluid and preparation method thereof

    CN117987102A

  • Workover fluid and preparation method and application thereof

    CN111269707A

  • Nanofiber reinforced foam system for foam drilling fluid and preparation method

    CN121343574A